Peran Perbankan Dalam Pencegahan Dan Pemberantasan Tindak Pidana Pencucian Uang Yang Dilakukan Oleh Nasabah - Pronika Julianti Manihuruk; Triono Eddy; Ahmad Fauzi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
Money laundering is rampant in Indonesia with banks as a means. Weaknesses in the banking system provide a loophole for money launderers to carry out their actions so that the proceeds of crime obtained are safely stored in banks. This research is a normative legal research that is descriptive in nature, with a case appoach. The purpose of this paper is to analyze the role of banks in effors to prevent and eradicate money laundering crimes committed by customers in the perspective of banking laws and the mode of action committed by money laundering criminals in banks. The results of this study indicate that themode of conduct of money laundering in conducting money laundering in banks is through capital cooperation though credit collateral, overseas transfers, disguising domestic businessses, engineering foreign loans and the role of banks in preventing and eradicating money laundering and banking laws by recognizing prospective customers who will open accounts in banks and monitoring customer profiles and transactions carried out on an on going basis, including conformity between transaction profile, examining the similarity or similarity of names with names suspects/defendants published in the mass media or by the competent authority.